2022
DOI: 10.1088/1755-1315/1001/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Newcastle Disease case on Kampung Unggul Balitbangtan (KUB) and Sentul Terseleksi (SenSi) chicken in Ungaran Research and Assessment Installation for Agricultural Technology

Abstract: Newcastle Disease (ND) is a common avian disease that attacks native chickens by causing respiratory problems, thereby leading to a high mortality rate of about 60% per year and economic losses in Indonesia. This study aims to determine the prevalence of ND in Kampung Unggul Balitbangtan (KUB) and Sentul Terseleksi (SenSi) chickens which was conducted from March to June 2021, on their cages at the Ungaran Research and Assessment Installation for Agricultural Technology. The total number of 20 serum KUB and Sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Population decline caused by the cages were used for other activities. The KUB chicken was limited on susceptible to diseases [17], however in 3 AEC's were highest mortality by AEC Bergas, AEC Ungaran Timur and AEC Ungaran Barat. Generally, chicken deaths are caused by physically pinched and pecked at each other even though it was reared in 10 chickens/m 2 .…”
Section: Body Weight Body Weight Gain and Mortality Ratementioning
confidence: 98%
“…Population decline caused by the cages were used for other activities. The KUB chicken was limited on susceptible to diseases [17], however in 3 AEC's were highest mortality by AEC Bergas, AEC Ungaran Timur and AEC Ungaran Barat. Generally, chicken deaths are caused by physically pinched and pecked at each other even though it was reared in 10 chickens/m 2 .…”
Section: Body Weight Body Weight Gain and Mortality Ratementioning
confidence: 98%
“…Pada periode starter membutuhkan suhu mulai dari 29˚C -35˚C, sedangkan pada periode finisher membutuhkan suhu 20˚C. Mengingat pertumbuhan memerlukan suhu yang konstan maka pada umumnya digunakanlah alat untuk menjaga suhu tersebut agar tetap konstan yaitu antara lain pada periode starter menggunakan brooder [4], [5] Selain dengan kebutuhan suhu, menurut [1] pada masa brooding, ayam juga membutuhkan cahaya penerangan yang cukup guna membantu peningkatan bobot badan. Nilai kebutuhan cahaya yang dibutuhkan pada masa brooding adalah antara 10-20 lux atau 20-40 watt untuk setiap m2.…”
Section: Pendahuluanunclassified
“…While Snot does not result in high mortality, it does lead to economic losses, primarily through a reduction in the chicken's body weight. The disease spreads easily in settings with suboptimal management[10]. Farmers reported that chickens exhibiting Snot symptoms typically presented with a swollen face, nasal mucus discharge, conjunctivitis, and occasionally displayed snoring and respiratory distress.…”
mentioning
confidence: 99%